Estudo da interação de fármacos em sistemas micelares formados por tween 80 por espalhamento de raios X a baixo ângulo - Santos, João Thiers Mendonça (2017)
Micelles are thermodynamically stable systems, formed after reaching a minimum concentration of surfactant in the solution, and is called the critical micellar concentration (CMC). The tensoactives are amphiphilic substances, that is, they have a polar region (head) and another apolar (tail) well defined in the molecular structure, being the tensoactive tween 80 chosen for this work. The CMC of this surfactant was found by ultraviolet-visible spectroscopy, through the absorption of a probe molecule that was ibuprofen at work. The CMC value is between 1.10-4 and 2.10-4 mM. Micelles have a great potential in the solubilization of poorly soluble drugs in aqueous solution that are being reused for different purposes than the current ones, besides taking drugs that have previously been abandoned due to their lack of solubility, for example in blood plasma, with we can increase the bioavailability of the same in the body, and can function as nanoreservatories of drugs thus minimizing the side effects of these, and help in the correct direction in which these drugs are discharged. Given this relevance, this work aims to understand how and where the interaction of the tween-80 formed micelles with the drugs, varying the pH and the concentrations of these. The drugs used in this study were carisoprodol, ibuprofen and sodium ibuprofen, since they have different characteristics in relation to the molecular polarity distribution. The technique used to perform these analyzes was the low angle X-ray scattering (SAXS), through which it is possible to analyze changes of shapes and sizes of the nanometric order. From the experimental observations, it was possible to say that for more effective interaction between the micelles and the drugs, it is necessary that they have a well defined and expressive apolar region, in terms of volume, in some region of the molecule, since the carisoprodol did not alter the SAXS curves of the micelles when it was present in the solution. Ibuprofen and sodium ibuprofen were able to cause significant changes in the SAXS curves, either in terms of low or high angle displacement or effects of attractive or repulsive interferences on the micelles. The modeling of the SAXS curves revealed the geometries acquired by the micelles, which at pH 4 and pH 7 alternated between a core and a cylindrical shell with an elliptical or circular cross-section depending on the drug or its concentration and at pH 9, The only cross section presented was elliptical geometry. The internal cylinder size of pH 4 micelles without drug was 33.9 Å, increasing to 43.4 Å with 30 mM ibuprofen and 53.7 Å with 30 mM ibuprofen sodium. At pH 7 and 9, there was little change in these lengths. A theoretical study was also carried out to better understand the micelle-drug interaction and, for this, the atomic charges, the polar and polar light, and the optimization of the structures of the substances used in this work were obtained. Tween 80 was optimized by the semi-empirical method PM3 (Parametric Method Number 3), while both carisoprodol and ibuprofen were optimized by the ab initio DFT (Density Functional Theory) method.